A Hybrid Magneto‐Optic Capacitive Memory with Picosecond Writing Time. (20th January 2023) - Rogers, Matthew; Habib, Ahasan; Teobaldi, Gilberto; Moorsom, Timothy; Johansson, J. Olof; Hedley, Luke; Keatley, Paul S.; Hicken, Robert J.; Valvidares, Manuel; Gargiani, Pierluigi; Alosaimi, Nader; Poli, Emiliano; et al.
Abstract: The long‐term future of information storage requires the use of sustainable nanomaterials in architectures operating at high frequencies. Interfaces can play a key role in this pursuit via emergent functionalities that break out from conventional operation methods. Here, spin‐filtering effects and photocurrents are combined at metal‐molecular‐oxide junctions in a hybrid magneto‐capacitive memory. Light exposure of metal‐fullerene‐metal oxide devices results in spin‐polarized charge trapping and the formation of a magnetic interface. Because the magnetism is generated by a photocurrent, the writing time is determined by exciton formation and splitting, electron hopping, and spin‐dependent trapping. Transient absorption spectroscopy measurements show changes in the electronic states as a function of the magnetic history of the device within picoseconds of the optical pumping. The stored information is read using time‐resolved scanning magneto optic Kerr effect measurements during microwave irradiation. The emergence of a magnetic interface in the picosecond timescale opens new paths of research to design hybrid magneto‐optic structures operating at high frequencies for sensing, computing, and information storage. Abstract : Excitons generated under light irradiation in a fullerene layer between a transition metal and a metal oxide are split due to interfacial dipolar electric fields, giving rise to a photocurrent that flows across the spin‐filtering fullerene‐oxide interface, leading to spin accumulation and writing a 2D magnetic layer in sub‐ps to ps timescales.